2015
DOI: 10.1371/journal.pone.0142442
|View full text |Cite
|
Sign up to set email alerts
|

The Efficient Derivation of Trophoblast Cells from Porcine In Vitro Fertilized and Parthenogenetic Blastocysts and Culture with ROCK Inhibitor Y-27632

Abstract: Trophoblasts (TR) are specialized cells of the placenta and play an important role in embryo implantation. The in vitro culture of trophoblasts provided an important tool to investigate the mechanisms of implantation. In the present study, porcine trophoblast cells were derived from pig in vitro fertilized (IVF) and parthenogenetically activated (PA) blastocysts via culturing in medium supplemented with KnockOut serum replacement (KOSR) and basic fibroblast growth factor (bFGF) on STO feeder layers, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Therefore, the development of in vitro models is required to study implantation processes. Bovine endometrial epithelial cells (EECs) are often used as a bovine in vitro model for studying the biological characteristics, cellular and molecular mechanisms, and responses to infection or damage of the bovine uterine epithelium, as well as for investigating the impacts of bovine embryo implantation and development of interactions between the embryo and mother (Bai et al 2014;Fortier et al 1988;Hou et al 2015;Skarzynski et al 2000;Zhang et al 2013). Coculture of bovine EECs and bovine trophoblast cells can be used to investigate the maturation of trophoblasts and the formation of binucleate cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of in vitro models is required to study implantation processes. Bovine endometrial epithelial cells (EECs) are often used as a bovine in vitro model for studying the biological characteristics, cellular and molecular mechanisms, and responses to infection or damage of the bovine uterine epithelium, as well as for investigating the impacts of bovine embryo implantation and development of interactions between the embryo and mother (Bai et al 2014;Fortier et al 1988;Hou et al 2015;Skarzynski et al 2000;Zhang et al 2013). Coculture of bovine EECs and bovine trophoblast cells can be used to investigate the maturation of trophoblasts and the formation of binucleate cells.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of PA blastocysts was 20.5%, which was lower than that in previous studies (> 29.6%, Hou et al . ; Sangho & Woo‐suk ). In the present study, we did not select mature oocytes after IVM culture because we performed IVF with cumulus‐enclosed oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that co-transfer of in vitro-produced embryos may be a promising avenue for achieving this goal, and two sources of embryos produced in vitro for cotransfer could be potentially utilized: (i) PA embryos and (ii) in vitro fertilization (IVF) embryos. Utilization of PA embryos has already been reported (Kawarasaki et al 2009), and we have shown that in vitro-matured (IVM)/IVF oocytes have the ability to develop to term even after in vitro culture (IVC) to the blastocyst stage (Nakamura et al 2017). In the present study, we compared the abilities of both PA and IVM/IVF oocytes to develop to the blastocyst stage, and their quality after in vitro culture.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations